HIKAYAT ‘ANEUK YATIM’ (Kajian Sosiologi Sastra Melalui Pendekatan Dialektika) - zulkhairi sofyan; Abzari Jafar (Jurnal Adabiya, 2021)
The saga 'Aneuk Yatim' written by Medya Hus is a reflection of Acehnese society which is presented in literary form. Sociology study of literature through dialectical approach to genetic structuralism is an option in this research, and also proves literature as a reflection of society. This saga tells, describes and tells the consequences of the conflict that occurred in Aceh, a saga that uses words that can describe the conditions of Aceh and what is experienced by the Acehnese people in general, the truth of the conflict that occurred in Aceh is represented in this saga when examined in more detail . In the plot, it is told about the splendor of Aceh, the condition of Aceh and how the Acehnese people respond to all of these.